Nigerian antimalarial ethnomedicine 2: Ethnobotanica surveys of herbal remedies used in the treatment of febrile illnesses in the middle belt of Nigeria (2002)
An ethnobotanical survey was conducted among residents of Gboko (urban) and Katsina Ala ( rural) local government areas in Benue state located in the middle belt of Nigeria. The Katsina-Ala and Gboko communities belong to the Tiv ethnic group. Documentation of the use of herbs as alternative in the treatment of fevers and identification of potential phytomedicines against malaria was done. Semi-structured questionnaires and focus group discussion guides were used to obtain information on description of febrile illness and utilization of herbal remedies for prevention and treatment. A total of 499 respondents comprising of mothers, fathers, community leaders/elders, herbs sellers and traditional healers were interviewed in the study. In the study, 9 types of febrile illnesses were proffered. The five most common type of febrile illnesses described were malaria (37.3%), yellow (28.8%), typhoid (27.3%), high fever (3.4%) and ordinary fever (0.5%). Perceived causes of febrile illness included mosquito bites, contamination of water and food, among others. Headache, general weakness, yellow coloration of eyes/uririe, elevated body temperature and diarrhoea, were the most common symptoms associated with febrile illnesses outlined by the respondents. Furthermore, malaria (81.5%) and high fever (57%) were reported to be common during the rainy season while typhoid (52%) is common during the dry season. Yellow fever was said to be non-dependent on season. Respondents believed children were more at risk of malaria compared with the other types of febrile illnesses mentioned. The respondents indicated that herbal recipes were effective treatment for Febrile illness. From the 105 recipes compiled, Azadirachto indica, Ficus thonningii, Annona senegalensis and Cymbopogon citratus were the most frequent herbs mentioned. Leaf (60.4%), was the most common part of plants used while boiling (92.5%), was frequently mentioned as method of herbal remedy preparation. The main route of administration of remedies mentioned was oral administration (97.9%). The study confirms the potential contribution of Phytomedicine to management of febrile illnesses, including malaria in the Tiv ethnomedicine.